Formação pedagógica do jesuíta missionário na América Portuguesa no século XVI - Prado, Wilson Da Silva (2019)
This work seeks to contribute to the reflection on education by analyzing the jesuitical formation, in particular the missionary Jesuit in Portuguese America in the 16th century. Firstly, based on the adopted reference, a reading of the initial documents of Jesuit formation, period letters, theater and other documents was sought, as well as a study of the context, in order to identify the initial formation of the member of the Society of Jesus and his transformations owing to the missionary action. The Jesuit is primarily formed in the Spiritual Exercises. Singular work of the founder of the Society of Jesus, Ignatius of Loyola, the Exercises seek to direct the will of the exerciser, so that he himself seeks to follow in the path that is pointed out. Thus, there is an internal movement of persuasion proposed by the Exercises in which, the greater the inner adhesion by who is practicing, the more effective it is. The Autobiography of Ignatius of Loyola, in its turn, was also written by the founder with pedagogical purpose, making the Society of Jesus member have in the idealization of Loyola`s person, a reference for his directed and uniform action. Another important document in the Jesuitical formation, the Constitutions of the Society of Jesus, serves to this standardization of the action and the regulation of the behavior. The Jesuit formed in this sense and in the context of Humanism, the Protestant Reformation and the Catholic Reformation, sought to act in conformity with this formation and worldview, through a pedagogy of the convincing of a free will, which he sought to conquer by persuasion and also by the use of force. In order to do this, he became a missionary in Portuguese America, where, in formal and informal education, in the schools and in the context of the villages, he experienced misunderstandings and divergences. This fact did not annul his formation, but complemented it, albeit in an unpredictable way, allowing to identify in the meetings and disagreements of the Jesuitical missionary activity in Portuguese America, in the cultural conflicts, in the formal and informal education, a pedagogical action originated from this relational action.